Penggunaan Tabel Keputusan Dalam Pembuatan Sistem Pengaturan Lampu Lalu Lintas Untuk Mengurangi Kemacetan Di Persimpangan - Sutariyani Sutariyani; Erlyna Dian Adityawati (Sekolah Tinggi Manajemen Informatika dan Komputer AUB - Indonesia, 2017)
Traffic congestion is one of the major problems that occur in large cities and generally occurs at crossroads. Traffic lights on one side will be very helpful in the fluency flow of traffic but on the other side even make the congestion worse. Many examples that occur are during rush hour and evening, Congestion occurs because the timing of traffic lights that are installed still use timing in normal traffic conditions. With such timing it will cause the buildup of vehicles on one side of the intersection and very susceptible to causing congestion. A good traffic control system will automatically adjust to the traffic flow density on the regulated path. An equipment system handled by the computer will feel more sophisticated, smarter, more automated, more practical, more efficient, safer, more thorough, and so on than if handled manually. In this research result of traffic light arrangement system using visual basic. Output of the system is the simulation of traffic engineering at the intersection. The criteria used include the number of deviations, the density of vehicles within a certain time, the width of the road and the direction of a one-lane road. Decision table created to determine the duration of the red and green lights, the green light flashed simultaneously, turn left the road continues and go straight path.Keywords : Decision tables, traffic light engineering, simulations.